Was there a Scientific Revolution? - Harrison, P (Cambridge University Press, 2007)
During the middle decades of the twentieth century the Scientific Revolution came to be understood as a key period in Western history. Recently, historians have cast doubt upon this category, questioning whether the relevant institutions and practices of the seventeenth century are similar enough to modern science to warrant the label ‘scientific’. A central focus of their criticisms has been the identity of natural philosophy—the major discipline concerned with the study of nature in the early modern period—and its differences from modern science. This paper explores the category of natural philosophy and its relation to philosophy more generally. It concludes that a significant philosophical revolution took place in the seventeenth century, and that this was important for the subsequent emergence of modern science.